Characterization of the mitochondrial genome of Eutomostethus vegetus Konow, 1898 (Hymenoptera: Tenthredinidae) and phylogenetic analysis - Li, Ya (Mitochondrial DNA B Resour, 2020)
The nearly complete mitochondrial genome of Eutomostethus vegetus Konow, 1898 was high-quality assembled. Several gene rearrangement events were observed in IQM gene cluster by comparing with the inferred insect ancestral mitochondrial genome. Phylogenetic analysis demonstrated the position of Eutomostethus vegetus in the Tenthredinidae and showed that Blennocampinae is a sister group to Fenusinae.